ASEAN WAY DALAM PERPEKTIF HUKUM INTERNASIONAL - Sefriani, Sefriani (Yustisia, 2014)
AbstractASEAN is not free from conflict among its members. For the example is Conflict between gunmen called themselves as representative of Sulu Kingdom with Malaysian policeman, conflict territory surrounding preh vihear temple between Cambodia and Thailand, conflict ambalat between Indonesia-malaysia potentially disturb peace and security of regional. Nothing done by ASEAN as organization which is most responsible to peace and stability at South East Asia Region. This matter caused by ASEAN way followed by ASEAN as conflict Resolution. ASEAN Way claim ASEAN applied non intervention to domestic affair of its member. ASEAN way claim also unanimous vote in decision making. ASEAN way often make ACEAN became contra productive toward existence of ASEAN itself. Constructive intervention or flexible engagement or enhanced interaction is solution offered to enhance ASEAN more advantage for South East Asia Region. AbstrakASEAN tidaklah bebas dari konflik antar anggotanya. Sebut saja beberapa waktu yang lalu konflik antara Sekelompok orang bersenjata yag menamakan dirinya perwakilan kerajaan Sulu dengan Pasukan Polisi Diraja Malaysia; konflik perbatasan di sekitar kuil preh vihear antara Kamboja dengan Thailand; Konflik kawasan ambalat antara Indonesia-Malaysia dan lain-lain yang berpotensi mengganggu   perdamaian dan keamanan regional. Tidak ada upaya sedikitpun yang dilakukan ASeAN sebagai organisasi yang paling bertanggung jawab terhadap perdamaian keamanan kawasan asia Tenggara. Hal ini diakibatkan oleh ASeAN Way yang merupakan mekanisme penyelesaian snegketa yang dianut oleh ASeAN yang menuntut ASeAN bersikap non intervensi terhadap urusan dalam negeri anggotanya. ASeAN Way juga menuntut pengambilan suara berdasarkan mufakat. Apa yang dianut ASeAN ini terkadang menjadi kontraproduktif terhadap keberadaan ASeAN. Constructive intervention atau yang disebut juga dengan flexible engagement, atau enhanced interaction merupakan solusi yang ditawarkan untuk mendorong agar keberadaan ASeAN menjadi lebih berarti bagi kawasan